Prosthetic therapy of the lateral facial defect - Lazić Vojkan; Đorđević Igor (Serbian Medical Society - Dental Section, Belgrade, 2012)
Introduction. Facial defects may arise as a result of head and neck trauma or facial tumor ablation. Minor defects can be reconstructed surgically while large defects usually need combined surgical and prosthetic reconstruction. The aim of this study was to present the prosthetic reconstruction of the lateral facial defect using facial colored acrylic prosthesis. Case Report. A male patient with a maxillary defect on the left side and a large lateral facial defect on the same side received an obturator prosthesis as well as a facial colored acrylic prosthesis (facial-orbit) retained by the glasses frame. Satisfied aesthetics was accomplished. However, the stability of the prostheses during mandibular movements could not be achieved which resulted in saliva leakage over the lips. Conclusion. Better functional and aesthetic outcome could be achieved by combined surgical and prosthetic treatment of such large facial defect.